Nanocomposite gas sensor based on covalently bonded carbon black-polymer and electronic nose system comprising the same

KR103020121B1Active Publication Date: 2026-09-16TAE SUNG ENVIRONMENT INST CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020250074685
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2026-09-16
Estimated Expiration
2045-06-09
Patent Text Reader

Abstract

A nanocomposite gas sensor and an electronic nose system comprising the same are disclosed, comprising: a polymer matrix; and carbon black particles dispersed within the polymer matrix and covalently connected to the polymer through a chemical reaction between a first functional group introduced on the surface and a second functional group introduced into the chain of the polymer matrix, wherein the first functional group is a carboxyl group (-COOH) and the second functional group is a hydroxyl group (-OH) and the covalent bond is an ester bond, or wherein the first functional group is a carboxyl group (-COOH) and the second functional group is an amine group (-NH2) and the covalent bond is an amide bond.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a gas sensor, in particular to a sensor for detecting volatile organic compounds (VOCs), and to an electronic nose system comprising the same. More specifically, the invention relates to a nanocomposite gas sensor and an electronic nose system comprising the same, wherein carbon black particles and a polymer matrix are connected by clear covalent bonds formed through controlled chemical reactions between specific functional groups, exhibiting excellent responsiveness to high concentrations of volatile organic compounds (VOCs), particularly significantly enhanced sensitivity. Background Technology

[0002] Volatile Organic Compounds (VOCs) are major substances requiring monitoring in various fields, including environmental pollution, indoor air quality degradation, and industrial safety. Various types of gas sensors have been developed to effectively detect these VOCs; among them, nanocomposite-based sensors, in which conductive fillers such as carbon black (CB) are dispersed within a polymer matrix, are attracting attention for their advantages such as room-temperature operation, low manufacturing costs, and flexibility. These carbon black / polymer nanocomposite sensors generally utilize the principle that when exposed to VOC vapors, the polymer matrix adsorbs specific VOCs and swells, causing a change in the conductive network formed between carbon black particles within the matrix (primarily an increase in resistance due to increased inter-particle distance). The performance of the sensor, particularly its sensitivity, depends significantly on how uniformly the carbon black particles are dispersed within the polymer matrix to form effective conductive pathways.

[0003] Patent documents 1 and 2 disclose sensor materials in which conductive particles, such as carbon black, are dispersed in a silicon-based polymer matrix, and attempts have been made to improve performance through control of particle type or size, crosslinking, etc. However, sensors based on simple physical mixing have inherent limitations in improving sensitivity because the movement of carbon black particles is restricted or irregular during polymer expansion, resulting in low efficiency of change in distance between particles. In addition, there were difficulties in ensuring dispersion stability or long-term reliability.

[0004] To overcome these limitations, there have been attempts to enhance the interaction between the carbon black surface and the polymer. For example, Patent Document 3 discloses a nanoconductive material and a polymer composite sensor, noting that surface graft modification can lower the percolation threshold and improve stability and reproducibility. Additionally, Patent Document 4 discloses a technique for preparing a covalently bonded composite powder by grafting a styrene-4-vinylpyridine copolymer onto a carbon black surface via radical polymerization and utilizing it as a sensor thin film. This document mentions the effect of improving sensitivity and linearity through covalent bonding. However, the method disclosed in Patent Document 4 involves grafting using radical polymerization; while this forms covalent bonds, reaction control is difficult, and the resulting bond structure may be non-uniform, such as having a wide distribution of grafted polymer chain lengths or the occurrence of side reactions. This differs from the clear formation of covalent bonds through controlled chemical reactions between predefined functional groups, which is the goal of the present invention. In addition, although Patent Document 4 presents a sensitivity improvement effect, it did not specifically satisfy the groundbreaking improvement in sensitivity to high concentrations of VOCs targeted by the present invention.

[0005] Therefore, there is a need to develop new sensor materials and high-performance sensors utilizing them that can dramatically improve detection sensitivity to high concentrations of VOCs and offer excellent reproducibility and stability by directly covalently bonding carbon black and polymers in a clearer and more controlled manner than existing methods. Prior art literature

[0006] Japanese Published Patent Application No. 2008-051795, U.S. Registered Patent Application No. 8012420, Chinese Registered Patent Application No. 110763737, Chinese Patent Application Publication No. 001963480 The problem to be solved

[0007] The present invention aims to solve the problems of the aforementioned prior art. One of the various objectives of the present invention is to provide a nanocomposite sensor material that exhibits significantly improved detection sensitivity compared to prior art by maximizing the efficiency of the change in distance between carbon black particles due to polymer expansion upon exposure to high concentrations of VOCs, through a structure in which carbon black and a polymer are directly connected by a clear covalent bond formed through a controlled chemical reaction between a specific first functional group on the surface of carbon black particles and a specific second functional group of a polymer chain.

[0008] In addition, another objective of the present invention is to provide a sensor element that exhibits excellent detection performance in a high-concentration VOC environment by including the high-sensitivity nanocomposite sensor material as a sensing layer, and an electronic nose system using the same. means of solving the problem

[0009] According to one aspect, a nanocomposite gas sensor is provided, comprising: a polymer matrix; and carbon black particles dispersed within the polymer matrix and covalently connected to the polymer through a chemical reaction between a first functional group introduced on the surface and a second functional group introduced into the chain of the polymer matrix, wherein the first functional group is a carboxyl group (-COOH) and the second functional group is a hydroxyl group (-OH) and the covalent bond is an ester bond, or the first functional group is a carboxyl group (-COOH) and the second functional group is an amine group (-NH2) and the covalent bond is an amide bond.

[0010] In one embodiment, the covalent bond is an ester bond or an amide bond formed through a reaction between a carboxyl group (-COOH) and a hydroxyl group (-OH) or an amine group (-NH₂), and the bond may be formed through a dehydration condensation reaction performed in the presence of a dehydrating agent.

[0011] In one embodiment, the dehydrating agent may be dichlorhexylcarbodiimide (DCC).

[0012] In one embodiment, the polymer constituting the polymer matrix comprises repeating units including hydroxyl groups (-OH) or amine groups (-NH₂), and the dehydrating agent may be used in an amount of 0.5 to 0.8 mol per 1 mol of carboxyl groups (-COOH) on the surface of the carbon black.

[0013] In one embodiment, the polymer constituting the polymer matrix includes a hydroxyl group (-OH) or an amine group (-NH₂) at the chain end, and the dehydrating agent may be used in an amount of 1.0 to 1.2 moles per mole of a carboxyl group (-COOH) on the surface of the carbon black.

[0014] In one embodiment, the polymer constituting the polymer matrix may be one or more selected from the group consisting of polyvinyl alcohol (PVA), cellulose derivative, poly(2-hydroxyethyl acrylate), poly(2-hydroxyethyl methacrylate), polyethyleneimine (PEI), polyethylene glycol (PEG) diol, polypropylene glycol (PPG) diol, polycaprolactone (PCL) diol, terminal amine group modified polyethylene glycol (PEG-NH₂), terminal amine group modified polypropylene glycol (PPG-NH₂), and polyamide.

[0015] In one embodiment, the polymer constituting the polymer matrix may include a hydroxyl group or an amine group at the chain end and may have a number average molecular weight (Mn) of 20,000 or less.

[0016] In one embodiment, the bond density, defined as the mass of the polymer connected by covalent bonds per 1g of carbon black, may be 0.05g to 2.0g.

[0017] In one embodiment, the nanocomposite gas sensor may further include additional carbon black particles or additional polymers for controlling initial electrical resistance or sensitivity, in addition to the carbon black particles and polymer matrix connected by covalent bonds.

[0018] According to another aspect, an electronic nose system is provided comprising: a sensor array including a plurality of gas sensors; and a pattern recognition unit that processes a signal output from the sensor array to identify the type of VOC. Effects of the invention

[0019] A nanocomposite gas sensor according to one aspect of the present invention can maximize changes in inter-particle distances by forming clear and controlled covalent bonds between carbon black particles and a polymer matrix, thereby allowing carbon black particles to effectively follow the movement of polymer chains during polymer expansion caused by the absorption of high concentrations of VOCs. As a result, compared to sensor materials manufactured by conventional simple physical mixtures or general grafting methods, it can exhibit the effect of significantly improving the sensitivity to changes in electrical resistance for high concentrations of volatile organic compounds (VOCs).

[0020] The aforementioned groundbreaking improvement in sensitivity is not merely a numerical improvement achieved as an extension of existing technology, but rather an advantageous effect resulting from a new structural feature of controlled covalent bonding between specific functional groups. In other words, it can be understood as being attributed to a new mechanism in which the strain generated when a polymer absorbs VOCs and expands is highly efficiently transduced into a change in resistance within the carbon black particle network through clear and strong covalent bonds formed between the carbon black and the polymer. This represents a level of performance improvement that is difficult to achieve with conventional grafting methods, such as physical mixing states where the interaction between carbon black and the polymer is weak, or radical polymerization, which are relatively difficult to control and where the bonding efficiency or location may be unclear.

[0021] Furthermore, strong covalent bonding between carbon black and polymers can enhance structural stability by increasing the interfacial bonding strength of the composite material. This can contribute to reducing performance degradation during repeated use of the sensor and improving long-term reliability and reproducibility.

[0022] In addition, by mixing additional carbon black or polymers into the grafted nanocomposite material, flexibility can be provided to finely adjust characteristics such as the initial electrical resistance or sensitivity of the sensor according to the application.

[0023] The effects of one aspect of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configurations described in the detailed description of this specification or the claims. Specific details for implementing the invention

[0024] The present invention will be described in more detail below. However, the present invention may be embodied in various different forms and should not be interpreted as being limited to the embodiments described herein. The embodiments presented in this specification are provided to clearly convey the disclosure of the present invention to those skilled in the art.

[0025] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may additionally include other components.

[0026] As used herein, the term “may” indicates that the applicable thing is a possibility or option, not that it must be so. Singular expressions include plural expressions unless the context clearly indicates otherwise.

[0027] Where a numerical range is described in this specification, unless otherwise specified, the range is interpreted to include a starting value and an ending value of the range, and to include all values ​​in between. For example, "1 to 5" includes not only 1 and 5 but also all values ​​between 1 and 5.

[0028] Additionally, when a numerical range is described in this specification, unless a specific range is otherwise described, the value has the precision of the significant figures provided according to the standard rules in chemistry for significant figures. For example, 10 includes a range of 5.0 to 14.9, and the number 10.0 includes a range of 9.50 to 10.49.

[0029] Nanocomposite material gas sensor

[0030] A nanocomposite gas sensor according to one aspect of the present invention comprises: a substrate; one or more pairs of electrodes formed on the substrate; and a sensing layer formed between the electrodes and comprising a nanocomposite material, wherein the nanocomposite material comprises a polymer matrix and carbon black particles dispersed within the polymer matrix and connected to the polymer matrix by a covalent bond. A key feature is that a covalent bond is formed through a specific chemical reaction between a first functional group introduced on the surface of the carbon black particles and a second functional group introduced into the polymer chain.

[0031] The carbon black particles described above act as conductive fillers and form an electrically conductive network within the polymer matrix. The type of carbon black used is not particularly limited, but particle size, specific surface area, and structure (e.g., DBP oil absorption) can be appropriately selected considering sensor characteristics (initial resistance, sensitivity, etc.). For example, carbon black with a high structure may be advantageous for forming a percolation network even at low content.

[0032] In the present invention, it is important to introduce a first functional group onto the surface of carbon black. The first functional group is a reactive group capable of forming a covalent bond by reacting with a second functional group of a polymer. In one embodiment, a carboxyl group (-COOH) can be introduced by oxidizing the surface of carbon black with nitric acid, sulfuric acid, hydrogen peroxide, ozone, etc. The carboxyl group can participate in a reaction with a hydroxyl group or an amine group, which will be described later.

[0033] In addition to this, amine groups (-NH₂), hydroxyl groups (-OH), isocyanate groups (-NCO), thiol groups (-SH), etc., may be introduced onto the surface of carbon black through known chemical modification methods. The type of the first functional group is selected by considering the reactivity with the second functional group of the polymer to be used.

[0034] The above polymer matrix serves as the matrix of the sensor material and exhibits selective swelling characteristics for specific VOCs. The type of polymer constituting the polymer matrix (hereinafter abbreviated as "polymer") can be selected considering its interaction with the target VOC (e.g., polarity / non-polarity, solubility parameters, etc.), processability, mechanical properties, etc. Importantly, the polymer must contain a second functional group capable of reacting with the first functional group of carbon black within the polymer chain or at its terminal.

[0035] The second functional group is a reactive group capable of reacting with the first functional group of the carbon black to form a covalent bond. For example, when a carboxyl group (-COOH) is introduced as the first functional group on the surface of the carbon black, the polymer may include a hydroxyl group (-OH) or an amine group (-NH2) as the second functional group. Additionally, when a thiol group (-SH) is introduced as the first functional group on the surface of the carbon black, the polymer may include a maleimide group as the second functional group. Furthermore, when an isocyanate group (-NCO) is introduced as the first functional group on the surface of the carbon black, the polymer may include a hydroxyl group (-OH) or an amine group (-NH2) as the second functional group.

[0036] The types of the above polymers are not specifically limited, but the following examples may be considered:

[0037] (a) A polymer having repeating units containing a hydroxyl group (-OH) or an amine group (-NH₂): e.g., polyvinyl alcohol (PVA), cellulose derivatives (e.g., hydroxypropyl cellulose), poly(2-hydroxyethyl acrylate), poly(2-hydroxyethyl methacrylate), etc., having repeating units containing a hydroxyl group (-OH); or a polymer having multiple amine groups (-NH₂) in the chain, such as polyethyleneimine (PEI).

[0038] (b) a polymer having a hydroxyl group or an amine group at the chain ends: e.g., a polymer having hydroxyl groups (-OH) at both ends, such as polyethylene glycol (PEG) diol, polypropylene glycol (PPG) diol, ethylene glycol-propylene glycol (EG-PPG) copolymer diol, polycaprolactone (PCL) diol, terminal hydroxyl group polybutadiene (HTPB); or a polymer having an amine group (-NH₂) at the ends, such as terminal amine group modified polyethylene glycol (PEG-NH₂), terminal amine group modified polypropylene glycol (PPG-NH₂), certain polyamides (e.g., amorphous nylon).

[0039] In the case of a polymer having a chain-terminal functional group of the above (b) group, it may be preferable to use one with a number average molecular weight (Mn) of 20,000 or less in order to sufficiently secure the functional group concentration.

[0040] The core of the present invention is to form a covalent bond between carbon black and a polymer through a specific chemical reaction between the first and second functional groups. This is a clear chemical bond distinct from simple physical adsorption or unclear interactions, and several key reaction examples are as follows.

[0041] Ester Linkage

[0042] It can be formed by reacting the carboxyl group (-COOH) of carbon black with the hydroxyl group (-OH) of the polymer. This reaction corresponds to a dehydration condensation reaction.

[0043] To carry out the reaction with high efficiency under mild conditions, it is desirable to use a dehydrating agent such as dichlorhexylcarbodiimide (DCC) and, if necessary, a catalyst such as 4-dimethylaminopyridine (DMAP).

[0044] When using DCC, the reaction can be carried out in a suitable organic solvent (e.g., DMF, DMSO, THF, etc.) at room temperature or under slightly heated conditions (e.g., 0-60°C).

[0045] At this time, it is important to control the reaction by adjusting the amount of dehydrating agent used according to the structure of the polymer used. For example, in the case of polymers containing multiple hydroxyl groups within repeating units, such as PVA or poly(2-hydroxyethyl acrylate) (PHEA), using an excessive amount of DCC can lead to excessive esterification and crosslinking, resulting in problems such as gelation. Therefore, in such cases, it is desirable to induce a partial reaction by using DCC at a level of 0.5 to 0.8 moles per mole of carboxyl groups on the carbon black surface. Additionally, excessive reactions can be controlled by adjusting the reaction temperature (e.g., 0-25°C) and time (e.g., 6-12 hours).

[0046] On the other hand, for polymers containing a limited number (e.g., 2) of hydroxyl groups at the chain ends, such as PEG diol or PPG diol, the risk of crosslinking is low, so it is desirable to increase reaction efficiency by using DCC at a level of 1.0 to 1.2 moles per mole of carboxyl groups on the carbon black surface.

[0047] Amide Linkage

[0048] It can be formed by reacting the carboxyl group (-COOH) of carbon black with the amine group (-NH₂ or -NHR) of the polymer. This reaction is also a dehydration condensation reaction, and amide bonds are generally chemically more stable than ester bonds.

[0049] This reaction can also be carried out efficiently using coupling reagents such as DCC (and, if necessary, HOBt (Hydroxybenzotriazole), etc.). Alternatively, methods such as converting the carboxyl group into an acid chloride by treating it with thionyl chloride (SOCl₂) and then reacting it with an amine may be used.

[0050] As with ester bonds, it is important to control the amount of dehydrating agent (DCC) used depending on the structure of the polymer used. For example, in the case of a polymer containing a number of amine groups within a repeating unit, such as PEI, it is desirable to use DCC at a level of 0.5 to 0.8 moles per mole of carboxyl group to prevent excessive amidation and crosslinking. On the other hand, in the case of a polymer containing a limited number of amine groups at the chain ends, such as PEG-NH₂, using DCC at a level of 1.0 to 1.2 moles per mole of carboxyl group may be advantageous in terms of reaction efficiency.

[0051] In addition to the reactions exemplified above, various covalent bond-forming reactions known in the art may be applied. For example, the thiol-maleimide click reaction, in which a thiol group (-SH) is introduced onto the surface of carbon black and reacted with a polymer having a maleimide group, or the reaction in which an isocyanate group (-NCO) is introduced onto the surface of carbon black and reacted with a polymer having a hydroxyl or amine group to form a urethane or urea bond may be considered. It is important that the reaction pathway is clear, side reactions are minimal, and control is easy so that efficient covalent bonding between carbon black and the polymer can be induced.

[0052] A nanocomposite gas sensor according to the present invention can be manufactured by applying a sensing layer containing the nanocomposite material onto a substrate on which an electrode is formed. For example, the insulating substrate may be a substrate having an oxide film (SiO₂) formed on a silicon wafer, a glass substrate, a ceramic substrate such as alumina, or a flexible plastic film such as polyethylene terephthalate (PET) or polyimide (PI). The electrode can typically be formed in the form of one or more pairs of opposing electrode patterns, for example, interdigitated electrodes (IDE), by using a material that has excellent electrical conductivity and is chemically stable, such as gold (Au), platinum (Pt), silver (Ag), or indium tin oxide (ITO), by methods such as lithography, deposition, or printing. The above-described sensing layer can be formed by applying the prepared nanocomposite material solution or suspension onto a substrate on which the electrode is formed using thin film formation techniques such as spin coating, drop casting, inkjet printing, or spray coating, and then undergoing a drying or heat treatment process at an appropriate temperature, for example, 60°C to 100°C, to remove the solvent. The thickness of the sensing layer can affect the response time and sensitivity of the sensor and can generally be controlled in the range of several hundred nanometers to several micrometers.

[0053] The operating principle of the sensor is as follows: When the sensor is exposed to an atmosphere containing target VOCs, the polymer matrix within the sensing layer selectively adsorbs specific VOC molecules based on their physical or chemical affinity. The adsorbed VOC molecules penetrate between the polymer chains, causing the polymer matrix to swell. At this time, carbon black particles, which are tightly connected to the polymer chains via covalent bonds, directly receive the expansion deformation of the polymer matrix and effectively move away from each other. This increases the average inter-particle distance much more efficiently than in cases where particles are simply physically mixed, have weak interfacial bonding forces (where carbon black particles may slide or rearrange during polymer expansion), or in general grafting where bonding efficiency or location is unclear. Since inter-particle distance in a conductive particle network is highly sensitive to charge transfer between particles (e.g., tunneling effects), this efficient increase in inter-particle distance causes a very large change (ΔR) in the total electrical resistance of the composite material. Consequently, the electrical resistance (R) measured between the two electrodes of the sensor... gas ) increases compared to the initial resistance (R0, resistance before VOC exposure). When VOCs around the sensor are removed, VOC molecules desorb from the polymer matrix, causing the polymer to contract again and the carbon black network to return to its original state, so the sensor resistance gradually returns to the initial state (R0). The magnitude of the sensor's response is generally the rate of change in resistance relative to the initial resistance (ΔR / R0=((R gas It is quantified as -R0) / R0)), and the sensor's sensitivity (k) is the value obtained by dividing the relative rate of change in resistance (ΔR / R0) relative to the sensor's initial resistance (R0) due to exposure to a specific concentration of volatile organic compounds (VOCs) by the concentration of the VOC (C, unit: ppm), i.e., k=((R gas It is defined as -R0) / R0) / C.

[0054] The sensor material of the present invention exhibits a much larger change in resistance for the same amount of polymer expansion, thereby exhibiting very high sensitivity. This significant improvement in sensitivity due to a specific covalent bond structure is a key technical feature of the present invention.

[0055] It is desirable to control the carbon black content in the above nanocomposite sensor material within a range that exceeds the percolation threshold to secure sufficient initial conductivity, while ensuring that it is not too high to hinder the expansion of the polymer or impede the processability of the material. Since the dispersibility of carbon black particles is improved and an effective conductive network can be formed due to covalent bonding, the desired initial resistance value can be achieved even at a lower content than in a physical mixing system. For example, to obtain a target initial resistance value (e.g., around several hundred kΩ), the carbon black content in the nanocomposite material of the present invention can be controlled to a range of 2 to 25 weight% relative to the total weight of the solid content (carbon black + polymer), for example, to a range of about 10 to 20 weight%, which may be lower than that of a comparative system without covalent bonding. The optimal range may vary depending on the type of carbon black used and the bonding density with the polymer.

[0056] The initial electrical resistance (R0) of the manufactured sensor material is typically 10 3 ~10 7 Ω range, e.g., 10 4 ~10 6 It can be adjusted within the Ω range, and the specific target resistance value may vary depending on the requirements of the measurement circuit used to connect the sensor element.

[0057] Graft density, which is the mass of polymers connected by covalent bonds per unit mass of carbon black, can affect sensor characteristics (sensitivity, response speed, recovery speed, etc.). For example, too low a graft density may prevent the covalent bonds from fully exerting their effects, while too high a graft density may restrict the mobility of polymer chains and hinder expansion. Therefore, it may be important to optimize the graft density for specific applications. According to one example, the graft density, that is, the mass of polymers connected by covalent bonds per 1g of carbon black, may be between 0.05g and 2.0g. Graft density can be measured by methods such as thermogravimetric analysis (TGA). For example, the graft density can be measured by calculating the mass of the covalently bonded polymer relative to the initial carbon black mass from the mass loss rate due to polymer degradation observed in a specific temperature range during TGA analysis. The above coupling density can be optimized according to required characteristics such as the sensitivity, response speed, recovery speed, and stability of the sensor, and preferably may be in the range of 0.1g to 1.5g / g, more preferably 0.2g to 1.0g / g, and most preferably 0.3g to 0.8g / g.

[0058] When a single polymer chain is bonded to multiple carbon black particles (acting as a crosslinker), or when the polymer chain itself has a branched structure or contains multiple reactive functional groups (e.g., multiple amine groups of PEI), the stability and mechanical properties of the carbon black-polymer network structure can be further enhanced. For example, when branched PEI is used as the polymer, a single PEI molecule can react with the -COOH groups on the surface of multiple carbon black particles to contribute to the formation of a network structure. Such a crosslinked structure can be advantageous in terms of the durability and long-term stability of the sensor film and can potentially affect recovery characteristics as well.

[0059] Selecting a polymer matrix by considering chemical similarity or interaction (e.g., polar-polar, non-polar, hydrogen bonding, etc.) with the target VOC can be important for the selectivity and sensitivity of the sensor. For example, for detecting polar VOCs such as formaldehyde and alcohol, it may be advantageous to use polymers containing polar hydroxyl groups or ether oxygen, such as PVA, PEG, and poly(2-hydroxyethyl acrylate). On the other hand, for detecting non-polar VOCs such as toluene and hexane, it may be effective to use polymers with strong non-polar characteristics, such as polysiloxane, polypropylene glycol (PPG), and polyisobutylene, by introducing appropriate reactive functional groups (e.g., terminal -OH or -NH₂).

[0060] The gas sensor described above generally comprises an insulating substrate, such as a silicon wafer, a glass substrate, an alumina ceramic substrate, or a flexible plastic film, and one or more pairs of opposing electrodes formed on the insulating substrate. The electrodes are formed by patterning with a conductive material such as gold, platinum, silver, or ITO. The nanocomposite material of the present invention is applied in a solution state between or covering the electrodes and dried to form a sensing layer. Various known techniques suitable for thin film formation, such as spun coating, dip coating, spray coating, inkjet printing, and screen printing, may be used as the application method. The thickness of the formed sensing layer can affect the response speed and sensitivity of the sensor and can generally be controlled within the range of hundreds of nanometers to tens of micrometers.

[0061] Furthermore, the covalently bonded nanocomposite material according to the present invention may be used as a sensor sensing layer on its own, but it may also be used by physically mixing it with additional carbon black particles (non-covalently bonded) or additional polymers (non-covalently bonded) to finely adjust the initial electrical resistance or sensitivity as needed. For example, a small amount of unmodified carbon black may be added to the prepared covalently bonded nanocomposite material to lower the initial resistance, or unreacted polymers may be added to control film-forming properties or adsorption characteristics for specific VOCs. Such additional mixing can provide a useful means for optimizing the final performance of the sensor for a specific application.

[0062] electronic nose system

[0063] A nanocomposite gas sensor according to one aspect of the present invention can be effectively applied to an electronic nose system that identifies various gases or odors by mimicking the human olfactory system.

[0064] An electronic nose system is characterized by comprising a sensor array including one or more nanocomposite material gas sensors according to one aspect of the present invention and a pattern recognition unit that processes a response signal from the sensor array.

[0065] An electronic nose is a device that mimics the human olfactory system to identify and analyze complex odors or gas mixtures. It generally consists of a sensor array composed of multiple gas sensors designed to have different sensitivity characteristics, a data acquisition unit that collects multidimensional response signal patterns obtained from each sensor, and a pattern recognition unit (e.g., a microprocessor equipped with a specific algorithm) that processes and interprets the collected patterns to identify the type of specific VOC or estimate its concentration. Pattern recognition algorithms that can be used include Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA), Support Vector Machine (SVM), and Artificial Neural Network (ANN).

[0066] The nanocomposite sensor material of the present invention enables the easy fabrication of sensors with diverse sensing characteristics by varying the type of polymer matrix used, the bonding method with carbon black, and the density. By configuring these fabricated high-sensitivity sensors into an array, a high-performance electronic nose system can be realized that effectively detects trace amounts of VOCs and has an enhanced ability to distinguish individual components even in complex gas environments. Since the covalent bond-based nanocomposite gas sensor according to the present invention exhibits significantly enhanced sensitivity and excellent stability, particularly for high concentrations of VOCs, including it in a sensor array is expected to improve the reliability and discriminative power of the overall response pattern of the sensor array, thereby greatly enhancing the overall performance of the electronic nose system, particularly the quantitative analysis capability and classification accuracy regarding various VOCs or complex odors.

[0067] The present invention will be explained in more detail below through specific embodiments. However, the following embodiments are merely illustrative of the present invention, and the scope of the present invention is not limited by the following embodiments.

[0068] Preparation Example 1: Preparation of Oxidized Carbon Black (OCB)

[0069] 10 g of commercially available carbon black (Manufacturer: Cabot, Product Name: Vulcan XC-72) was added to 200 mL of a 60 wt% aqueous nitric acid solution and refluxed with stirring at 80°C for 3 hours using an oil bath. After the reaction, the mixture was cooled to room temperature, and the excess nitric acid was removed by repeating the processes of centrifugation and redispersion with distilled water until the pH of the washing solution became neutral. The obtained solid precipitate was freeze-dried or dried in a vacuum oven at 60°C for 24 hours to obtain oxidized carbon black (OCB) powder with carboxyl groups (-COOH) introduced to the surface. As a result of analyzing the surface functional groups of OCB using an FT-IR spectrometer (Manufacturer: PerkinElmer, Model Name: Spectrum Two), an absorption peak corresponding to the C=O stretching vibration of the carboxyl group was clearly observed around 1720 cm¹, confirming the introduction of the carboxyl group. As a result of measurement by Boehm titration, the total acid group content was found to be approximately 1.0–1.2 mmol / g. This can be used to estimate the amount of reaction sites in subsequent covalent reactions.

[0070] Example 1: Preparation of OCB-PPG Nanocomposite Material

[0071] 0.85 g of polypropylene glycol diol (PPG diol, manufacturer: Sigma-Aldrich, number average molecular weight Mn=8,000 g / mol) was added to 20 mL of tetrahydrofuran (THF, manufacturer: Samchun Chemicals, 99.8%) and completely dissolved at room temperature using a magnetic bar. 0.15 g of the OCB prepared in Preparation Example 1 was added to this, and a uniform OCB dispersion was prepared by dispersing for 1 hour using an ultrasonic disperser (manufacturer: Sonics & Materials, model name: VCX 750, output 40%, pulse on / off 5 sec / 5 sec). Here, 1.1 g of dichlorhexylcarbodiimide (DCC, Manufacturer: Sigma-Aldrich, 99%) (corresponding to approximately 1.1 equivalents relative to the molar amount of -COOH contained in 0.2 g of OCB, calculated based on the total acidic group content of OCB measured in Preparation Example 1, which was approximately 1.1 mmol / g) and 0.2 g of 4-dimethylaminopyridine (DMAP, Manufacturer: Sigma-Aldrich, 99%) were added as catalysts, and the mixture was stirred for 24 hours at room temperature (25°C) under a nitrogen atmosphere to carry out an ester bonding reaction between the carboxyl groups (-COOH) on the surface of the OCB and the hydroxyl groups (-OH) at the ends of the PPG chains. After the reaction, the insoluble byproduct dichlorhexylurea (DCU) generated was removed by filtration using a PTFE membrane filter with a pore size of 0.45 μm. The obtained solution was slowly added dropwise to 500 mL of an excess of distilled water while stirring to precipitate the solid product. The precipitated solid was separated by filtration, washed several times with distilled water to remove unreacted materials and residual solvent, and then dried in a vacuum oven at 60°C for 24 hours to obtain the final product, OCB-PPG nanocomposite powder.

[0072] Example 2: Preparation of OCB-PHEA Nanocomposite Material

[0073] 0.87 g of poly(2-hydroxyethyl acrylate) (PHEA, assuming Mn=15,000 g / mol) was added to 20 mL of dimethylformamide (DMF) and dissolved at room temperature. 0.13 g of the OCB prepared in Preparation Example 1 was added to this, and a homogeneous OCB dispersion was prepared by ultrasonically dispersing under the same conditions as in Example 1. To this, 0.6 g of dichlorhexylcarbodiimide (DCC) (corresponding to approximately 0.6 equivalents relative to the molar amount of -COOH contained in 0.2 g of OCB, calculated based on the total acid group content of OCB measured in Preparation Example 1, which was approximately 1.1 mmol / g) and 0.1 g of DMAP were added as catalysts, and the mixture was stirred for 10 hours under a nitrogen atmosphere and cooling conditions of 0-5°C to carry out an ester bonding reaction between the carboxyl groups (-COOH) on the surface of the OCB and the hydroxyl groups (-OH) of the PHEA chain. The DCU removal and post-treatment process after the reaction was performed similarly to Example 1, but 500 mL of ethanol or isopropanol was used as the non-solvent for precipitation. Finally, OCB-PHEA nanocomposite powder was obtained.

[0074] Example 3: Preparation of OCB-PEG-NH₂ Nanocomposite Material

[0075] 0.87 g of terminal amine-modified polyethylene glycol (PEG-NH₂, Mn=8,000 g / mol) was added to 20 mL of dimethyl sulfoxide (DMSO) and dissolved. 0.13 g of the OCB prepared in Preparation Example 1 was added to this, and a uniform OCB dispersion was prepared by ultrasonically dispersing under the same conditions as in Example 1. Here, 1.1 g of dichlorhexylcarbodiimide (DCC) (corresponding to approximately 1.1 equivalents relative to the molar amount of -COOH contained in 0.2 g of OCB, calculated based on the total acid group content of OCB measured in Preparation Example 1, which was approximately 1.1 mmol / g) and 0.6 g of hydroxybenzotriazole (HOBt) were used as coupling additives, and the mixture was stirred for 24 hours at room temperature (25°C) under a nitrogen atmosphere to carry out an amide bonding reaction between the carboxyl groups (-COOH) on the surface of the OCB and the amine groups (-NH₂) at the ends of the PEG chains. After the reaction, the DCU removal and post-treatment process was performed similarly to Example 1, but 500 mL of diethyl ether was used as a non-solvent for precipitation. Finally, an OCB-PEG-NH₂ nanocomposite powder was obtained.

[0076] Comparative Example 1: Preparation of OCB / PPG Physical Mixture

[0077] 0.85 g of polypropylene glycol diol (PPG diol, Mn=8,000 g / mol) was dissolved in 20 mL of THF and cooled to room temperature. 0.15 g of OCB prepared in Preparation Example 1 was added to this, and the mixture was dispersed for 1 hour using an ultrasonic disperser under the same conditions as in Example 1. An OCB / PPG mixed solution was prepared in a simply mixed state without covalent bonding reactions, without adding coupling reagents such as DCC or DMAP.

[0078] Experimental Example 1: Fabrication of Sensor Element and Evaluation of VOC Sensitivity Characteristics

[0079] Sensor devices were fabricated using the covalently bonded nanocomposite powders obtained in Examples 1 to 3 and the physical mixing solution of Comparative Example 1. In the examples, the obtained powders were redispersed in suitable solvents such as THF, DMF, and DMSO to prepare a solution for coating the sensor film. In Comparative Example 1, the prepared physical mixing solution was used as is.

[0080] Each of the solutions prepared in this way was uniformly coated onto an alumina substrate having a gold (Au) interlocking electrode formed thereon using spin coating or the like. The coated substrate was dried at 100°C for 2 hours to form a sensing layer.

[0081] The fabricated sensor elements were mounted in a custom-made gas sensor measurement system (SourceMeter: Keithley 2400, gas mixer: MFC-based), and dry air (synthetic air, relative humidity < 5%) was flowed at a flow rate of 100 mL / min at room temperature (25℃) until the initial resistance (R0) of each sensor element stabilized (variation rate < 1% / 10 min). Subsequently, a specific VOC vapor corresponding to each sensor was mixed with the dry air using a mass flow controller (MFC) and flowed into the sensor chamber for 5 minutes at a total flow rate of 100 mL / min. The sensor sensitivity (k) is the maximum resistance value (R) upon gas exposure. gas Using ), k=((R gas -R0) / R0) / C (where R0 is the initial resistance, R gas ε₀ is the resistance value after 5 minutes of VOC exposure, and C is the gas concentration (ppm). At least three devices were fabricated and measured for each sensor type, and the average value was used. The results are shown in Table 1 below.

[0082] division Target VOC VOC concentration (ppm) Initial resistance (R0, kΩ) Sensitivity (k, ppm -1 ) Example 1 THF 200,000 517.5 1.52×10 -1 Example 2 CH3OH 150,000 412.8 5.21×10 -1 Example 3 CH3OH 150,000 458.1 8.31×10 -1 Comparative Example 1 THF 200,000 633.2 4.21×10 -3

[0083] The results in Table 1 above clearly demonstrate the technical effects of the present invention. It can be confirmed that Examples 1 to 3, in which carbon black and a polymer are covalently linked through a specific chemical reaction according to the present invention, exhibit a significantly higher sensitivity (k) to specific high-concentration VOC exposure compared to Comparative Example 1, which is simply physically mixed without covalent bonding. For example, the sensitivity of Example 1 to 200,000 ppm THF was approximately 36 times higher than that of Comparative Example 1, and the sensitivities of Examples 2 and 3 to 150,000 ppm methanol were approximately 120 times and nearly 200 times higher, respectively, than the sensitivity of Comparative Example 1 to THF. This strongly suggests that a mechanism is at work in which covalent bonding very efficiently transmits polymer expansion deformation to changes in the resistance of the carbon black network. These results clearly demonstrate that the specific covalent bond formation method of the present invention brings about a qualitatively different level of sensitivity improvement, rather than merely a gradual improvement.

[0084] Experimental Example 2: Evaluation of Long-term Stability and Reproducibility

[0085] To evaluate the long-term performance stability and response reproducibility of the sensors, a process of repeatedly exposing each sensor element (Examples 1 to 3 and Comparative Example 1) to specific high-concentration VOC vapors corresponding to each sensor and then recovering was performed. Specifically, Example 1 and Comparative Example 1 were exposed to 200,000 ppm THF vapor, and Example 2 and Example 3 were exposed to 150,000 ppm methanol vapor for 5 minutes, followed by a recovery process involving flowing dry air for 10 minutes, which was repeated 100 times. The baseline resistance (R0) value at the start of each cycle (dry air exposure state) was recorded, and the baseline resistance change rate (drift, %) over 100 cycles was calculated. In addition, the response reproducibility was evaluated by calculating the relative standard deviation (RSD, %) of the maximum resistance change rate (ΔR / R0) values ​​measured in each cycle. The results are summarized in Table 2 below.

[0086] Example 1 Example 2 Example 3 Comparative Example 1 Base resistance drift(% @ 100 cycles) 4.2% 3.5% 3.8% 28.5% Response reproducibility (△R / R0RSD @ 100 cycles) 4.8% 4.1% 4.3% 20.5%

[0087] As shown in the results of Table 2, all Examples (1, 2, and 3) exhibited significantly lower base resistance drift and smaller response RSD values ​​compared to Comparative Example 1, demonstrating excellent long-term stability and reproducibility. For example, after 100 repeated measurements, the base resistance change rate of the Examples was less than 5% and the response reproducibility (RSD) was also less than 5%, indicating very stable performance, whereas Comparative Example 1 showed significant fluctuations in base resistance and large response deviations. This experimentally proves that the strong covalent bonds formed in the present invention significantly enhance the interfacial bonding strength between the carbon black particles and the polymer matrix, thereby maintaining the structural durability of the sensor and effectively suppressing performance degradation even under repeated swelling / shrinkage stress caused by exposure to high concentrations of VOCs. Therefore, the sensor of the present invention possesses the significant advantage of providing stable and reliable measurement results even with long-term use.

[0088] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form. The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and their equivalents should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A nanocomposite gas sensor comprising: a polymer matrix; and carbon black particles dispersed within the polymer matrix and covalently connected to the polymer through a chemical reaction between a first functional group introduced on the surface and a second functional group introduced into the chain of the polymer matrix; wherein the polymer constituting the polymer matrix is ​​one or more selected from the group consisting of polypropylene glycol (PPG) diol, poly(2-hydroxyethyl acrylate) (PHEA), and terminal amine group modified polyethylene glycol (PEG-NH2), and the number average molecular weight (Mn) of the polymer is 8,000 or more and 20,000 or less, and wherein the first functional group is a carboxyl group (-COOH) and the second functional group is a hydroxyl group (-OH) and the covalent bond is an ester bond, or wherein the first functional group is a carboxyl group (-COOH) and the second functional group is an amine group (-NH2) and the covalent bond is an amide bond. Claim 2 A nanocomposite gas sensor according to claim 1, wherein the covalent bond is an ester bond or an amide bond formed through a reaction between a carboxyl group (-COOH) and a hydroxyl group (-OH) or an amine group (-NH₂), and the bond is formed through a dehydration condensation reaction performed in the presence of a dehydrating agent. Claim 3 A nanocomposite gas sensor characterized in that, in paragraph 2, the dehydrating agent is dichlorhexylcarbodiimide (DCC). Claim 4 A nanocomposite gas sensor according to claim 3, characterized in that the polymer constituting the polymer matrix is ​​poly(2-hydroxyethyl acrylate) (PHEA), and the dehydrating agent is used in an amount of 0.5 to 0.8 mol per 1 mol of carboxyl groups (-COOH) on the surface of the carbon black. Claim 5 A nanocomposite gas sensor according to claim 3, wherein the polymer constituting the polymer matrix is ​​polypropylene glycol (PPG) diol and / or terminal amine group modified polyethylene glycol (PEG-NH2), and the dehydrating agent is used in an amount of 1.0 to 1.2 moles per mole of carboxyl groups (-COOH) on the surface of the carbon black. Claim 6 delete Claim 7 delete Claim 8 A nanocomposite gas sensor according to claim 1, characterized in that the bond density, defined as the mass of the polymer connected by covalent bonds per 1g of carbon black, is 0.05g to 2.0g. Claim 9 A nanocomposite gas sensor according to claim 1, characterized in that, in addition to the carbon black particles and polymer matrix connected by covalent bonds, the nanocomposite gas sensor further comprises additional carbon black particles or additional polymers for controlling initial electrical resistance or sensitivity. Claim 10 An electronic nose system comprising: a sensor array including a plurality of gas sensors according to any one of claims 1 to 5, 8 and 9; and a pattern recognition unit that processes a signal output from the sensor array to identify the type of VOC.

Citation Information

Patent Citations

  • Sensor and sensor material for detecting pathogen-derived volatile organic compounds

    JP2025509426A